2007
DOI: 10.1038/nn2032
|View full text |Cite
|
Sign up to set email alerts
|

Focal brain damage protects against post-traumatic stress disorder in combat veterans

Abstract: Post-traumatic stress disorder (PTSD) is an often debilitating mental illness that is characterized by recurrent distressing memories of traumatic events. PTSD is associated with hypoactivity in the ventromedial prefrontal cortex (vmPFC), hyperactivity in the amygdala and reduced volume in the hippocampus, but it is unknown whether these neuroimaging findings reflect the underlying cause or a secondary effect of the disorder. To investigate the causal contribution of specific brain areas to PTSD symptoms, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
190
1
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(209 citation statements)
references
References 35 publications
11
190
1
7
Order By: Relevance
“…Flashback memories consist of sudden involuntary, yet vivid, remembrances of specific memories during a traumatic event that are devoid of context. Frequently associated with amygdala hyperactivity (Koenigs et al, 2008), flashback memories may relate to selective semantically primed memories, dissociated from contextual encoding (cf. Newport & Nemeroff, 2000;Skelton, Ressler, Norrholm, Jovanovic, & Bradley-Davino, 2012), as illustrated by iEEG data.…”
Section: Clinical Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Flashback memories consist of sudden involuntary, yet vivid, remembrances of specific memories during a traumatic event that are devoid of context. Frequently associated with amygdala hyperactivity (Koenigs et al, 2008), flashback memories may relate to selective semantically primed memories, dissociated from contextual encoding (cf. Newport & Nemeroff, 2000;Skelton, Ressler, Norrholm, Jovanovic, & Bradley-Davino, 2012), as illustrated by iEEG data.…”
Section: Clinical Significancementioning
confidence: 99%
“…Second, while iEEG data reviewed above present little evidence of long-term contextual encoding, it is plausible that the stimuli in the reviewed studies remained below a level of biological significance strong enough to induce synaptic longterm potentiation needed to induce contextual conditioning (Sah, Westbrook, & Luthi, 2008). Ample evidence illustrates the amygdala's role in contextual learning under fear conditioning scenarios (Fanselow & LeDoux, 1999;Sah et al, 2008) in rodents (Chau, Prakapenka, Fleming, Davis, & Galvez, 2013;Flavell & Lee, 2012;Trogrlic, Wilson, Newman, & Murphy, 2011) and in human neuroimaging (Hughes & Shin, 2011) and lesion (Koenigs et al, 2008) studies. As none of the iEEG studies reviewed used a conditioning task, future iEEG research would benefit from employing context learning paradigms controlling for arousal, self-relevance, and threat in order to assess the full nature of selective encoding and potential contextual encoding in human amygdala neurons relative to fear and anxiety-related behaviors in healthy and clinical populations (Brocke et al, 2010).…”
Section: Clinical Significancementioning
confidence: 99%
“…For example, recent neuroimaging data support the concept that the exaggerated amygdala response due to mPFC and hippocampal functional deficits may be associated with exaggerated fear reexperiencing in PTSD patients (15,18). Moreover, in Vietnam War veterans who suffered brain injury and emotionally traumatic events, a substantially reduced occurrence of PTSD symptoms was found in individuals with damage to the ventromedial PFC and/or the anterior temporal area that included the amygdala (19). These results further suggest that the mPFC and amygdala are critically involved in the pathogenesis of PTSD (14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 91%
“…Moreover, in Vietnam War veterans who suffered brain injury and emotionally traumatic events, a substantially reduced occurrence of PTSD symptoms was found in individuals with damage to the ventromedial PFC and/or the anterior temporal area that included the amygdala (19). These results further suggest that the mPFC and amygdala are critically involved in the pathogenesis of PTSD (14)(15)(16)(17)(18)(19). A recent clinical study reported that, in PTSD patients, a down-regulation of Allo levels in cerebrospinal fluid (CSF) was correlated with increased PTSD reexperiencing and comorbid depressive symptoms (20).…”
mentioning
confidence: 99%
“…The Vietnam Head Injury Program (VHIP) evaluated veterans with moderate or severe combat TBI who had penetrating cerebral injuries [49]. TBI was classified based on lesion location, and the prevalence of PTSD was compared across groups with different injury loci.…”
Section: Variablementioning
confidence: 99%